A Secure and Effective Content Transmission in Content Based Networks Using Bloom Cast - Hemanjali, S; Krishna, IMV (International Journal of Computer Sciences and Engineering, 2025)
P2P network stands amidst one of the best and attractive network tool. This approach made the allocation of contents through internet accessible. For unstructured P2P networks Bloom Cast deliver as an efficient technique for text sending scheme. In order to conclude a guaranteed recall at a communication cost of the network, Bloom Cast makes copies of the capacity in the network constantly at a random across the P2P networks. To abutment random node sampling and network size appraisal Bloom Cast appropriate its hybrid network which is an aggregate of a lightweight DHT (distributed hash table) and an unstructured P2P overlay. There are prospects of malicious codes and false agreement in unstructured P2P networks. At times it achieves false identities resulting in false activity with other character. The normal method here uses the conception of DHT and influence management which arrange efficient file transmission. In the expected system, we propose a novel strategy, called Bloom Cast, an efficient and effective full-text transportation scheme, in satisfied networks. The query demand independent archetype strategy, we propose a novel strategy, called Bloom Cast, to support efficient and adequate text transmission. Bloom Cast are mathematically that the recall can be guaranteed at a communication cost of O (square root N), where N is the size of the network.